A comprehensive study on regulatory requirements for development and filing of generic drugs globally - Handoo, Shweta; Arora, Vandana; Khera, Deepak; Nandi, Prafulla Kumar; Sahu, Susanta Kumar (International Journal of Pharmaceutical Investigation)
The regulatory requirements of various countries of the world vary from each other. Therefore, it is challenging for the companies to develop a single drug which can be simultaneously submitted in all the countries for approval. The regulatory strategy for product development is essentially to be established before commencement of developmental work in order to avoid major surprises after submission of the application. The role of the regulatory authorities is to ensure the quality, safety, and efficacy of all medicines in circulation in their country. It not only includes the process of regulating and monitoring the drugs but also the process of manufacturing, distribution, and promotion of it. One of the primary challenges for regulatory authority is to ensure that the pharmaceutical products are developed as per the regulatory requirement of that country. This process involves the assessment of critical parameters during product development.
Keywords: Development; drug; generic; global; regulatory